BUDAYA SAPRAHAN SEBAGAI REFLEKSI INTEGRASI BERBANGSA DAN BERNEGARA DI ERA DIGITAL - Sutoyo Budiharo; Ziqri Muhammad Hafiidz (Jurnal Budaya Nusantara, 2023)
The issue of hoaxes in the digital era is growing massively on social media. The issue of hoaxes can divide the life of the nation and state. What's more, individualism accompanied by ego becomes a very frightening specter. Therefore, the need for a culture that can reflect the life of the nation and state, especially in the current digital era. This study aims to describe the culture of saprahan as a reflection of the integration of the nation and state in the digital era. The approach used in this study is a qualitative approach, through ethnographic studies. The sampling technique used purposive sampling technique. The method used to obtain data by means of interviews and documentation. The data analysis technique used is the interaction data analysis technique belonging to Miles and Huberman, consisting of data reduction, data presentation, and conclusion/verification. Based on the data analysis that has been done, Saprah Culture is an eating culture consisting of small groups equipped with Saprah dishes that are sufficient to accommodate 6 people. Inside Saprah's dish are various kinds of side dishes, vegetables, and chili sauce. In serving the food, there are standard protocols and must be heeded. In the Saparahan culture, there are philosophical values, togetherness values and etiquette values, which are good for living as a nation and as a state in the digital era. The meaning of consensus contained in Saprahan culture as a form of reflection on nation and state is very useful and in accordance with the practice of the fourth precept in Pancasila.